Inter-machine plasma perturbation studies in EU-DEMO-relevant scenarios: lessons learnt for prediction of EM forces during VDEs. (1st July 2022) - Sias, G.; Minucci, S.; Lacquaniti, M.; Lombroni, R.; Fanni, A.; Calabrò, G.; Cannas, B.; Pisano, F.; Siccinio, M.; Ramogida, G.; Giorgetti, F.; Fanelli, P.; et al.
Abstract: To support the deployment of the DEMO wall protection strategy, the development of comprehensive analyses is essential to understand the implications of transient perturbations on plasma shape control and on vertical stability, some of the most critical aspects to be considered in elongated plasmas. The design activities of the DEMO limiter structures require a deep understanding of the effects induced by transient plasma perturbations coupled with one of the most severe load conditions to occur in tokamaks, the vertical displacement event (VDE). Since electromagnetic (EM) loads during VDE phases are among the DEMO limiter's design drivers, this study focuses on predictive simulations of the final plasma position and of EM loads following a VDE. For this purpose, a multi-tokamak study, supported by the construction of an inter-machine database containing experimental transient plasma perturbations and VDEs from JET and ASDEX Upgrade (AUG), has been carried out. It aims to characterize some transient plasma perturbations that may lead to high control efforts by the vertical stability system in terms of variations of the plasma's internal parameters and vertical displacements. Consequently, such experimental transient plasma perturbations have been properly scaled to DEMO reference geometries with different magnetic configurations, to be simulated in terms of plasma dynamical behaviour by means of MAXFEA code. Finally, initial predictive EM loads on DEMO limiter structures are discussed in the case of VDEs following plasma perturbations.